Critical Factors impact Artificial Intelligence Implementation in Supply Chain Management. Case study Danang SMEs - Trinh Le Tan; Ngo Huu Kim Nguyen; Nguyen Ho Thanh Tuong Vi; Ho Thanh Nha; Truong Thi Thuy; Tran Thanh Danh (Journal of Interdisciplinary Socio-Economic and Community Study, 2022)
The purpose of this paper is to research the elements that affect the decision to implement Artificial Intelligence (AI) in supply chain management at SMEs in Da Nang, Vietnam. The application of new technologies in supply chain management is extremely important during the development period of industry 4.0, and a more in-depth examination of the issues in implementing AI to the supply chain will provide a more objective perspective on the challenges and benefits of adopting AI to supply chain management in SMEs. This paper investigates the effect factors in the implementation of Artificial Intelligence (AI) technology by constructing a Technology-Organization-Environment (TOE) framework. In our research, we use qualitative research to build hypotheses. A structured questionnaire with a five-point Likert scale was distributed to 120 SMEs in Da Nang to collect data for quantitative research, analytical techniques, first to check the reliability and validity of the tool used, then perform exploratory factor analysis EFA, Pearson correlation, and multiple regression analysis. The results indicated that the complexity factor, compatibility factor, cost factor, and external pressure factor are not important factors that influence AI implementation. Referring to those technical factors (relative advantages), organization factors (top management support, organization readiness) and environment factor (government support) have a positive influence on the technology implementation of AI in supply chain management.